2017
DOI: 10.3347/kjp.2017.55.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium and Giardia and the Relationship between Protozoa and Water Quality Indicators in Swimming Pools

Abstract: A total of 60 samples were collected from 35 swimming pools in Beijing, China, and the presence of Cryptosporidium and Giardia were investigated. The results showed that 16.7% and 15.0% of samples were positive for Cryptosporidium oocyst and Giardia cysts, respectively, with a mean concentration of 0.30 oocysts/10 L and 0.27 cysts/10 L. The oocysts and cysts were found to have higher rates of occurrence in August than in May. Genotyping confirmed the presence of Cryptosporidium hominis, C. parvum, and Giardia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Cryptosporidium oocysts have been detected in various water bodies, which have caused over 524 waterborne outbreaks of cryptosporidiosis worldwide, and most of them are linked to drinking water and recreational water (particularly swimming pools) [16][17][18]. In China, although no waterborne outbreaks have been reported, Cryptosporidium oocysts have been detected in source and tap water [62][63][64] as well as swimming pools [65,66]. In a study conducted in Shanghai, well water as the drinking water supply had higher risk for human Cryptosporidium infection than tap water and hand pump water [S1 Table reference list-73].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Cryptosporidium oocysts have been detected in various water bodies, which have caused over 524 waterborne outbreaks of cryptosporidiosis worldwide, and most of them are linked to drinking water and recreational water (particularly swimming pools) [16][17][18]. In China, although no waterborne outbreaks have been reported, Cryptosporidium oocysts have been detected in source and tap water [62][63][64] as well as swimming pools [65,66]. In a study conducted in Shanghai, well water as the drinking water supply had higher risk for human Cryptosporidium infection than tap water and hand pump water [S1 Table reference list-73].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…On the other hand, both protozoa have also been found in urban wastewater 16 , surface drinking water sources 17 19 and recently in treated recreational waters (i.e. swimming pool waters) 20 . However, little is known about their occurrence in untreated recreational water.…”
Section: Introductionmentioning
confidence: 99%
“…Due to being a natural reservoir for many pathogens, water could make the patient more susceptible to infections. The risk of disease or infection associated with swimming pools is mainly due to the fecal contamination of the water, which may be caused by feces released by swimmers or sources of contaminated water (20) , which was confirmed in a study that identified Cryptosporidium and Giardia in swimming pools, leading to the occurrence of outbreaks among swimmers (21) .…”
Section: Note: CVI = Content Validity Indexmentioning
confidence: 87%